Android Application Schema Model Development in PJOK Curriculum 2013 for Class XI Students in SMA/SMK/MA - Priyatama, Alfian; Rahayu, Setya; Soenyoto, Tommy (Journal of Physical Education and Sports, 2019)
Technological advances greatly support teaching and learning activities for teachers and students in schools. Android applications on smartphones make it easy to communicate to get access to various information. The purpose of this study is to develop an Android-based application that contains a PJOK scheme in class XI SMA/SMK/MA which includes Core Competency (KI), Basic Competency (KD) and content. This research is a Research and Development study. The research instrument used a questionnaire with research subjects, namely curriculum experts, multimedia/information technology experts, and class XI students SMA/SMK/MA. The results of the validation by curriculum experts in stage 1 with a score of 3.3 or 66% included category "good" and stage 2 with a score of 4.2 or 84% included category "very good." Validation by multimedia experts in stage 1 with a score of 3.6 or 71% included category of "good" and stage 2 with a score of 4.5 or 90% included category "very good." The results of the small-scale effectiveness test with a rating score of 3.2 or 63% are included category "good." The results of a large-scale effectiveness test with a rating score of 4.2 or 83% are category "very good." The conclusion that the android application product physical, sports and health education subjects in Curriculum 2013 for class XI SMA/SMK/MA is effectively used as a learning resource for students.